Practical Quantum Private Database Queries Based on Passive Round-Robin Differential Phase-shift Quantum Key Distribution - Li, Jian (Sci Rep, 2016)
A novel quantum private database query protocol is proposed, based on passive round-robin differential phase-shift quantum key distribution. Compared with previous quantum private database query protocols, the present protocol has the following unique merits: (i) the user Alice can obtain one and only one key bit so that both the efficiency and security of the present protocol can be ensured, and (ii) it does not require to change the length difference of the two arms in a Mach-Zehnder interferometer and just chooses two pulses passively to interfere with so that it is much simpler and more practical. The present protocol is also proved to be secure in terms of the user security and database security.